Insulin/IGF signaling in Drosophila and other insects: factors that regulate production, release and post-release action of the insulin-like peptides - Nässel, Dick R; Broeck, Jozef Vanden (Cellular and molecular life sciences : CMLS, 2016)
Insulin, insulin-like growth factors (IGFs) and insulin-like peptides (ILPs) are important regulators of metabolism, growth, reproduction and lifespan, and mechanisms of insulin/IGF signaling (IIS) have been well conserved over evolution. In insects, between one and 38 ILPs have been identified in each species. Relatively few insect species have been investigated in depth with respect to ILP functions, and therefore we focus mainly on the well-studied fruitfly Drosophila melanogaster. In Drosophila eight ILPs (DILP1-8), but only two receptors (dInR and Lgr3) are known. DILP2, 3 and 5 are produced by a set of neurosecretory cells (IPCs) in the brain and their biosynthesis and release are controlled by a number of mechanisms differing between larvae and adults. Adult IPCs display cell-autonomous sensing of circulating glucose, coupled to evolutionarily conserved mechanisms for DILP release. The glucose-mediated DILP secretion is modulated by neurotransmitters and neuropeptides, as well as by factors released from the intestine and adipocytes. Larval IPCs, however, are indirectly regulated by glucose-sensing endocrine cells producing adipokinetic hormone, or by circulating factors from the intestine and fat body. Furthermore, IIS is situated within a complex physiological regulatory network that also encompasses the lipophilic hormones, 20-hydroxyecdysone and juvenile hormone. After release from IPCs, the ILP action can be modulated by circulating proteins that act either as protective carriers (binding proteins), or competitive inhibitors. Some of these proteins appear to have additional functions that are independent of ILPs. Taken together, the signaling with multiple ILPs is under complex control, ensuring tightly regulated IIS in the organism.